Decoding the codon usage patterns in Y-domain region of hepatitis E viruses - Zoya Shafat; Anwar Ahmed; Mohammad K. Parvez; Shama Parveen (Journal of Genetic Engineering and Biotechnology, 2022)
Abstract Background Hepatitis E virus (HEV) is a positive-sense RNA virus belonging to the family Hepeviridae. The genome of HEV is organized into three open-reading frames (ORFs): ORF1, ORF2, and ORF3. The ORF1 non-structural Y-domain region (YDR) has been demonstrated to play an important role in the HEV pathogenesis. The nucleotide composition, synonymous codon usage bias in conjunction with other factors influencing the viral YDR genes of HEV have not been studied. Codon usage represents a significant mechanism in establishing the host-pathogen relationship. The present study for the first time elucidates the detailed codon usage patterns of YDR among HEV and HEV-hosts (Human, Rabbit, Mongoose, Pig, Wild boar, Camel, Monkey). Results The overall nucleotide composition revealed the abundance of C and U nucleotides in YDR genomes. The relative synonymous codon usage (RSCU) analysis indicated biasness towards C and U over A and G ended codons in HEV across all hosts. Codon frequency comparative analyses among HEV-hosts showed both similarities and discrepancies in usage of preferred codons encoding amino acids, which revealed that HEV codon preference neither completely differed nor completely showed similarity with its hosts. Thus, our results clearly indicated that the synonymous codon usage of HEV is a mixture of the two types of codon usage: coincidence and antagonism. Mutation pressure from virus and natural selection from host seems to be accountable for shaping the codon usage patterns in YDR. The study emphasised that the influence of compositional constraints, codon usage biasness, mutational alongside the selective forces were reflected in the occurrence of YDR codon usage patterns. Conclusions Our study is the first in its kind to have reported the analysis of codon usage patterns on a total of seven different natural HEV hosts. Therefore, knowledge of preferred codons obtained from our study will not only augment our understanding towards molecular evolution but is also envisaged to provide insight into the efficient viral expression, viral adaptation, and host effects on the HEV YDR codon usage.